2020
DOI: 10.1108/mbe-02-2020-0033
|View full text |Cite
|
Sign up to set email alerts
|

Key factors influencing word-of-mouth intentions: the case of college freshmen in Taiwan

Abstract: Purpose This study aims to examine the key determinants of word-of-mouth intentions among freshmen in a Taiwanese college. It investigates the causal relationships among different indicators of organizational sustainable development. Design/methodology/approach An empirical study is conducted on a sample of 3,159 college freshmen. A survey instrument with 41 measurement items are used to recognize the implementation of management practices at the college level. Descriptive statistical and multiple regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…WOM influences tourist perception (Herle, 2018). Good satisfaction also generates a positive effect in WOM (Hsu et al, 2020).…”
Section: Tourist Behavioural Intentionmentioning
confidence: 98%
“…WOM influences tourist perception (Herle, 2018). Good satisfaction also generates a positive effect in WOM (Hsu et al, 2020).…”
Section: Tourist Behavioural Intentionmentioning
confidence: 98%
“…Voyer and Ranaweera (2015) reported that in-service purchase decisions, WOM reduces consumers' level of perceived risk and uncertainty. The effectiveness of WOM is well accepted in different service industries; i.e., tourism (Albarq, 2014;Ali et al, 2019), restaurants (Muzamil et al, 2018;Jalilvand et al, 2017), health care (Martin, 2017;Chen et al, 2018), and higher education (Hsu, 2020;Chen, 2016). The difficulty in quality DOI: 10.52633/jemi.v3i2.79…”
Section: Introductionmentioning
confidence: 99%